Cytotoxic Effect and TLC Bioautography-Guided Approach to Detect Health Properties of Amazonian Hedyosmum sprucei Essential Oil. (28th March 2016) - Guerrini, Alessandra; Sacchetti, Gianni; Grandini, Alessandro; Spagnoletti, Antonella; Asanza, Mercedes; Scalvenzi, Laura
Abstract : Bioautography has been used as rapid and easy strategy to detect and identify bioactive fractions/molecules in the never before investigated Hedyosmum sprucei Solms (Chloranthaceae) essential oil (EO). The antioxidant activity, performed through DPPH bioautographic assay and spectrophotometric evaluations (IC50 = 230 ± 10 µ g/mL), seemed to be mainly due to α -cadinol and α -muurolol. (HP)TLC bioautography, focused on antimicrobial capacities, pointed out α -cadinol, α -muurolol, τ -muurolol, caryophyllene oxide, and methyleugenol as the most effective compounds against Staphylococcus aureus, considered as testing strain. Moreover, the microdilution method, assessed among a wide panel of microorganisms, revealed Listeria grayi and Staphylococcus aureus as the most sensitive among human tested strains and Clavibacter michiganensis among phytopathogens. GC-MS chemical profile showed that bioactive molecules represented only a small quantity of the whole EO: germacrene D (23.16%), β -caryophyllene (15.53%), δ -cadinene (5.50%), α -copaene (5.08%), and α -phellandrene (3.48%) were the main compounds, highlighting an uncommon composition among the genus Hedyosmum . Finally, H. sprucei EO was checked for cytotoxic potential against A549 (lung cancer) and MCF-7 (breast cancer) cell lines showing promising cytotoxic effects against both cell lines after 48 h (IC50 A549 = 44.05 ± 2.35 µ g/mL; IC50 MCF-7 = 32.76 ± 4.92 µ g/mL) and 72 h (IC50 A549 = 43.55 ± 2.80 µ g/mL; IC50 MCF-7 = 33.64 ± 0.43 µ g/mL).